Concentrated Dual-Salt Electrolyte to Stabilize Li Metal and Increase Cycle Life of Anode Free Li-Metal Batteries. Issue 8 (1st January 2019) - Beyene, Tamene Tadesse; Bezabh, Hailemariam Kassa; Weret, Misganaw Adigo; Hagos, Teklay Mezgebe; Huang, Chen-Jui; Wang, Chia-Hsin; Su, Wei-Nien; Dai, Hongjie; Hwang, Bing-Joe
Abstract : Anode-free batteries (AFBs) are impressive and recent phenomena in the era of energy storage devices due to their high energy density and relative ease of production compared to the traditional Lithium metal batteries (LMBs). However, dendrite formation during plating and stripping and low coulombic efficiency (CE) are the main challenges that impede practical implementation of these batteries. Here we report an extremely stable dual-salt electrolyte, 2M LiFSI+1M LiTFSI (2FSI+1TFSI)) in DME/DOL (1:1, v/v), system in comparison to the single salt 3M LiTFSI (3TFSI) in DME/DOL (1:1, v/v), to effectively stabilize AFB composed of LiFePO4 cathode and bare Cu-foil anode for the first time. The electrolyte stabilized anode-free cell with the configuration Cu||LiFePO4 via reductive decomposition of its anions and enabled the cell to be cycled with CE of 98.9% for 100 cycles. This results from the formation of stable, ion conductive and electrically insulating inorganic components rich Solid Electrolyte Interface (SEI) layer on the surface of in-situ deposited Li-metal that blocks the undesirable parasitic reaction between the deposited Li and the electrolyte. Thus, aforesaid SEI mitigates formation of dead lithium and dissolution of the in-situ deposited Li surface during repeated cycling and prolongs cycle life of the battery.